MECHANISMS FOR REGULATING STUDENTS’ NATIONAL MUSICAL VALUES IN THE DIGITAL ENVIRONMENT WITHIN THE FRAMEWORK OF THE DEVELOPMENT STRATEGY - Nazarova Dilnoza Eraliyevna,Berdiyeva Nozima Faxriddin qizi (Journal of Applied Science and Social Science, 2026)
This article examines the mechanisms for regulating and developing students’ national musical values in the digital educational environment within the framework of the national development strategy. In the context of globalization and rapid digital transformation, students become acquainted with music not only in the traditional classroom environment, but also through social networks, online platforms, mobile applications and multimedia resources. This situation creates both new opportunities and certain challenges for preserving national musical heritage and developing students’ aesthetic taste, musical consciousness and cultural identity. The purpose of the study is to identify pedagogical, methodological and socio-cultural mechanisms that contribute to the effective transmission of national musical values in the digital environment. The research is based on the methods of scientific-theoretical analysis, content analysis, comparative analysis and pedagogical generalization. The results show that the development of national musical values among students requires the interconnected application of organizational-pedagogical, informational-methodological, socio-cultural and monitoring mechanisms. In conclusion, it can be noted that, when used purposefully and systematically with pedagogical support, digital technologies can become an effective means of strengthening students’ musical culture and national identity.